Intelligent Serverless Process Automation for Scalable Cloud Operations and Dynamic Resource Optimization - Sridhar Mahadevan, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
Cloud providers have created serverless platforms which abstract theentire operational management of applications and provide pay-per-use billing.Although this service alleviates the operational complexity for application service development and hosting, the increase in service offerings also resultingin a consolidation of applications hosted by customers on one single